Functional mobility decline and incident mild cognitive impairment and early dementia in community-dwelling older adults: the Singapore Longitudinal Ageing Study. (3rd September 2022) - Ng, Tze Pin; Lee, Tih Shih; Lim, Wee Shiong; Chong, Mei Sian; Yap, Philip; Cheong, Chin Yee; Rawtaer, Iris; Liew, Tau Ming; Gwee, Xinyi; Gao, Qi; Yap, Keng Bee
Abstract: Background: Motor and gait disturbances are evident in early Alzheimer and non-Alzheimer dementias and may predict the likelihood of mild cognitive impairment (MCI) or progression to dementia. Objective: We investigated the Timed-Up-and-Go (TUG) measure of functional mobility in predicting cognitive decline and incident MCI or early dementia (MCI–dementia). Design: Prospective cohort study with 4.5 years follow-up. Setting: Population based. Participants: 2, 544 community-dwelling older adults aged 55+ years. Methods: Participants with baseline data on TUG, fast gait speed (GS), knee extension strength (KES) and performance-oriented mobility assessment (POMA) gait and balance were followed up for cognitive decline (Mini-Mental State Exam; MMSE drop of ≥2, among 1, 336 dementia-free participants) and incident MCI–dementia (among 1, 208 cognitively normal participants). Odds ratio (OR) and 95% confidence intervals (95% CI) were adjusted for age, sex, education, smoking, physical, social and productive activity, multi-morbidity, metabolic syndrome and MMSE. Results: Per standard deviation increase in TUG, POMA, GS and KES were significantly associated with incident MCI–dementia: TUG (OR = 2.84, 95% CI = 2.02–3.99), GS (OR = 2.17, 95% CI = 1.62–2.91), POMA (OR = 1.88, 95% CI = 1.22–2.92) and KES (OR = 1.52, 95% CI = 1.15–2.02). Adjusted OR remained significant only for TUG (OR = 1.52, 95% CI = 1.01–2.31) and GS (OR = 1.53, 95% CI = 1.08–2.16). Areas under the curve (AUC) for TUG (AUC = 0.729, 95% CI = 0.671–0.787) were significantly greater than GS (AUC = 0.683, 95% CI = 0.619–0.746), KES (AUC = 0.624, 95% CI = 0.558–0.689) and POMA (AUC = 0.561, 95% CI = 0.485–0.637). Similar associations with cognitive decline were significant though less pronounced, and adjusted ORs remained significant for TUG, GS and POMA. Conclusion: Functional mobility decline precedes incident MCI and early dementia. The TUG appears to be especially accurate in predicting the future risks of adverse cognitive outcomes. Trial Registration: ClinicalTrials.gov NCT03405675. Registered 23 January 2018 (retrospectively registered).